A multicarrier QAM modulator for WCDMA base-station with on-chip D - Kosunen, M.
In this paper, design and implementation of a multicarrier quadrature amplitude modulation (QAM) modulator for a wideband code division multiple access (WCDMA) base-station with a 14-bit on-chip D/A converter is described. The modulator is capable of modulating four carriers with four independent in phase (I) and quadrature (Q) data streams. The proposed modulator structure consists of an interpolation chain for data streams and four digital frequency synthesizer/modulators, which are based on a coordinate rotation digital computer (CORDIC) vector rotation algorithm. The interpolation chain consists of a root-raised cosine pulse shaping filter and three half-band filters for image filtering. The modulated carriers are combined to form a multicarrier WCDMA signal. The SINC-attenuation effect of a digital/analog (D/A) converter is canceled by an inverse-SINC predistortion filter. The multicarrier signal is converted to the analog domain with a 14-bit current steering D/A converter, which is integrated on the same silicon chip. The modulator is implemented with a 0.35-mum BiCMOS process with CMOS transistors only
Keywords: 0.35 micron; 14 bit; BiCMOS process; CMOS transistors; SINC attenuation effect; Si; WCDMA base station; Coordinate rotation digital computer vector rotation algorithm; Current steering D/A converter; Four digital frequency modulators; Four digital frequency synthesizer; Image filtering; Interpolation chain; Inverse SINC predistortion filter; Modulated carriers; Modulator structure; Multicarrier QAM modulator; Multicarrier WCDMA signal; Multicarrier quadrature amplitude modulation modulator; On-chip D/A converter; Quadrature data streams; Root raised cosine pulse shaping filter; Silicon chip; Three half band filters; Wideband code division multiple access base station